Microglia in Alzheimer Disease: Well-Known Targets and New Opportunities - Hemonnot, Anne-Laure; Hua, Jennifer; Ulmann, Lauriane; Hirbec, Hélène (Frontiers in Aging Neuroscience, 2019)
Microglia are the resident macrophages of the central nervous system. They play key roles in brain development and physiology during life and aging. Equipped with a variety of molecular sensors and through the various functions they can fulfil, they are critically involved in maintaining the brain’s homeostasis. In Alzheimer disease (AD), microglia reaction was initially thought to be incidental and triggered by amyloid deposits and dystrophic neurites. However, recent genome-wide association studies have established that the majority of AD risk loci are found in or near genes that are highly and sometimes uniquely expressed in microglia. This leads to the concept of microglia being critically involved in the early steps of the disease and identified them as important potential therapeutic targets. Whether microglia reaction is beneficial, detrimental or both to AD progression is still unclear and the subject of intense debate. In this review, we are presenting a state-of-knowledge report intended to highlight the variety of microglial functions and pathways shown to be critically involved in AD progression. We first address both the acquisition of new functions and the alteration of their homeostatic roles by reactive microglia. Second, we propose a summary of new important parameters currently emerging in the field that need to be considered to identify relevant microglial targets. Finally, we discuss the many obstacles in designing efficient therapeutic strategies for AD and present innovative technologies that may foster our understanding of microglia roles in the pathology. Ultimately, this work aims to fly over various microglial functions to make a general and reliable report of the current knowledge regarding microglia’s involvement in AD and of the new research opportunities in the field.